De Nieuwe Tijd : sociaaldemokratisch maandschrift. (Amsterdam : J.A. Fortuyn, 1895)
Bibliotheek Camille Huysmans
Hoofdredactie: Henriette Roland Holst, F. Van Der Goes, H. Gorter, Herman Heyermans jr. (1901), J. Saks, F.M. Wibaut (feb 1908)
Redactie: W.H. Vliegen, F.M. Wibaut, K. Kautsky, H. Van Kol, P.J. Troelstra, H. Spiekman, H. Polak
Drukker/Drukkerij: Amst. Boek-en Steendrukkerij
Nederlands
Periodiek